DNA and some laboratory tests of nematode suppressing efficient soil isolates of Aspergillus niger - M. ARSHAD ANWER, MUJEEBUR RAHMAN KHAN* and (Indian Phytopathology, 2008)
Sixteen isolates of Aspergillus niger collected from different crop fields were subjected to RAPD- PCR using 20 Operon primers and 8 synthetic primers. Twenty two primers led to amplification of 727 fragments ranging from 3500 bp (OPA-11) to 200 bp (Primer-06), and two bands were found to be monomorphic where as rest of them polymorphic. Three amplicons produced by OPA-16 were recorded as isolate specific as 2300 bp by AnC2 and AnR3, and 2800 bp by AnC2 only. High degree of genetic similarity (0.79) was measured between AnC2 and AnR3 and least similarity (0.17) between AnC2 and AnR2 . Multivariate analysis of genetic similarity have revealed three major clusters categorized as Group I, Group II and Group III. The isolates AnC2 and AnR3 , which produced highest amount of siderophore, HCN, NH3 and solubilized greatest amount of phosphorus belonged to a subgroup of Group I. When eggmasses of Meloidogyne incognita were incubated in the culture filtrate of the isolates of A. niger the egg hatching was greatly suppressed and 28 to 100% mortality in the hatched juveniles was recorded. Pot experiment conducted to examine the effect of A. niger isolates on the development of root-knot caused by M. incognita on eggplant showed significant (PÂ£0.001) suppressing in the galling and egg mass production and a decrease in the soil population of the nematode.